2015
DOI: 10.1210/en.2015-1070
|View full text |Cite
|
Sign up to set email alerts
|

KNDy Neurons Modulate the Magnitude of the Steroid-Induced Luteinizing Hormone Surges in Ovariectomized Rats

Abstract: Kisspeptin is the most potent stimulator of LH release. There are two kisspeptin neuronal populations in the rodent brain: in the anteroventral periventricular nucleus (AVPV) and in the arcuate nucleus. The arcuate neurons coexpress kisspeptin, neurokinin B, and dynorphin and are called KNDy neurons. Because estradiol increases kisspeptin expression in the AVPV whereas it inhibits KNDy neurons, AVPV and KNDy neurons have been postulated to mediate the positive and negative feedback effects of estradiol on LH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 82 publications
4
34
1
2
Order By: Relevance
“…Our results show that the expression of ARC Kiss1 mRNA co‐varies with circulating LH levels, with RFRP‐3 acting to reduce both Kiss1 mRNA expression and circulating concentrations of LH in the afternoon but not in the morning, consistent with this pathway of control. In support of this possibility, ablation of ARC kisspeptin neurones leads to atypical LH surge amplitude . The present findings are also in agreement with a recent study demonstrating RFRP‐3 suppression of ARC kisspeptin expression in free‐cycling Syrian hamsters maintained in long photoperiods .…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that the expression of ARC Kiss1 mRNA co‐varies with circulating LH levels, with RFRP‐3 acting to reduce both Kiss1 mRNA expression and circulating concentrations of LH in the afternoon but not in the morning, consistent with this pathway of control. In support of this possibility, ablation of ARC kisspeptin neurones leads to atypical LH surge amplitude . The present findings are also in agreement with a recent study demonstrating RFRP‐3 suppression of ARC kisspeptin expression in free‐cycling Syrian hamsters maintained in long photoperiods .…”
Section: Discussionsupporting
confidence: 93%
“…Specificity was demonstrated by the preservation of neuropeptide Y, proopiomelanocortin, and GnRH neuronal elements in the arcuate nucleus and adjacent median eminence (31). Dopamine neurons are also preserved after injections of NK 3 -SAP (32), consistent with the lack of NK 3 R receptor on arcuate neurons that project to the fenestrated capillaries in the median eminence (33).…”
mentioning
confidence: 75%
“…In the ewe, dynorphin neurons in the arcuate nucleus mediate the inhibition of GnRH pulses by P (72,73). Interestingly, a recent study showed that injection of a -opioid receptor agonist into the preoptic area increases the E 2 -induced LH surge, similar to their amplification of the LH surge after NK 3 -SAP injections into the arcuate nucleus (32). Finally, central infusion of a -opioid receptor agonist on proestrous afternoon markedly amplifies the LH surge, suggesting that endogenous -opioid tone limits the size of the preovulatory LH surge in intact rats (74).…”
mentioning
confidence: 98%
“…Yet, AVPV Kiss1 gene expression is decreased after prolonged (48 hours) fasting [Kalamatianos et al, 2008], which suggests that ARH and AVPV kisspeptin neurons may impose effects of acute versus persistent metabolic imbalance on GnRH. Recent studies show that ARH kisspeptin/neurokinin B/dynorphin (KNDy) neurons may regulate the LH surge via dynorphin signaling to the AVPV [Helena et al, 2015]. The present work introduces the novel premise that these cells may mediate rapid hypoglycemic repression of the LH surge.…”
Section: Discussionmentioning
confidence: 91%